Diachronic Change in Verbal Agreement Patterns with Majorité. (15th July 2013) - Tristram, Anna
Abstract This article is concerned with the description of data relating to a case of morphosyntactic variation and change in French: verbal agreement patterns with the noun majorité 'majority'. Quantitative analysis of apparent‐time data from cloze ('gap‐fill') tests suggests that plural agreement with this noun is increasing; data from a diachronic corpus study confirm that this is the case. A number of factors are found to constrain this variation and change, including most importantly the presence and number of a post‐modifying noun phrase (e.g. la majorité des hommes). The implications of these findings for the definition of collective nouns in French are discussed.